2010
DOI: 10.1002/cncr.25254
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the development of brain metastases

Abstract: BACKGROUND The risk of developing brain metastases after definitive treatment of locally advanced nonsmall cell lung cancer (NSCLC) is approximately 30%-50%. The risk for patients with early stage disease is less defined. The authors sought to investigate this further and to study potential risk factors. METHODS The records of all patients who underwent surgery for T1-T2 N0-N1 NSCLC at Duke University between the years 1995 and 2005 were reviewed. The cumulative incidence of brain metastases and distant metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(60 citation statements)
references
References 55 publications
5
54
1
Order By: Relevance
“…In our series, on multivariate analysis, non-squamous cell cancer histology and LNR ≥ 30 % were associated with an increased risk of developing BM and BM as the first relapse. Non-squamous cell cancer as risk factor of BM and BM as the first relapse is consistent with many,[11,13-15,20,23,32-36] but not all,[7,8,10,12,19,22,31,37-39] previous studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our series, on multivariate analysis, non-squamous cell cancer histology and LNR ≥ 30 % were associated with an increased risk of developing BM and BM as the first relapse. Non-squamous cell cancer as risk factor of BM and BM as the first relapse is consistent with many,[11,13-15,20,23,32-36] but not all,[7,8,10,12,19,22,31,37-39] previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Larger tumor size is associated with an increased risk of BM. [39] Bajard et al demonstrated that in a cohort of 305 stage I–IIIB patients, T4 was related with a higher risk of BM, compared with T1–3. [34] However, many other investigators did not find that T status was significantly related with the risk of BM.…”
Section: Discussionmentioning
confidence: 99%
“…However, these special immunostaining markers are not used in routine pathological evaluation. Several recent studies evaluated LVI with routine HE staining and elastica-van Gieson staining, and demonstrated an association between LVI and disease recurrence [23,24,25,26,27]. The additional effect of the special immunostaining markers should be further validated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, it has been shown that there is a 40% increase in EGFR expression in brain metastases compared to primary breast tumors (27). Additionally, non-small cell lung cancer (NSCLC) has a high frequency of activating EGFR gene alterations and a high incidence of metastasis to the brain (107109). Considering these results it may indicate EGFR drives metastatic tumors toward the brain and/or the brain microenvironment and provides a selective pressure toward EGFR genetic alterations.…”
Section: Role Of Egfr In Breast Cancer Brain Metastasismentioning
confidence: 99%